The Implementation of Appraisal Information System to Enhance Education Personnel Performance: Evidence from Universitas Negeri Malang - Fitria Puji Harmini; Abdul Hakim; Ike Wanusmawatie (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2021)
This study aims at explaining the relationship between work performance appraisal information systems, work performance appraisals and the performance of education personnel. This research was included in the category of explanatory research with a quantitative approach using survey methods to obtain a detailed understanding of the phenomenon. This research was conducted at Universitas Negeri Malang which is one of the leading state universities in East Java, and has implemented an information system for work performance appraisal for the last five years. Thus, it will be interesting to know whether the information system has a sustainable impact or not on improving employee performance. The sample of this study was 328 education personnel who are state civil servants at the head office of Universitas Negeri Malang. The results showed that the information system and work performance appraisal had a positive impact on the performance of education personnel. Furthermore, both information systems and performance appraisal simultaneously also have a positive influence on the performance of education personnel.Keywords: Work Performance Appraisal, Information Systems, Employee Performance